Critical Evaluation of the case Rajesh Sharma and others v. State of U.P. and another, AIR 2017 SC 3869, under section 498 of Indian Penal Code. - Dhere, Vidya Vasantrao; Bendale, Ujwala (International Journal of Psychosocial Rehabilitation, 2020)
This article shades light on the injustice towards women, although there is criminal law made to protect women. Few false cases doesn’t nullify the essence of the Section 498A, IPC, but such cases has created doubts in the minds of the Judges and so they started giving directions to curb them and protect the husbands and his family. The author tries to portray the mindset of Judges and wants that every individual case is different and so there cannot be any generalized statement about it.